Greening residential area through cleaner production strategies during planning stage / Logheshwaran M.S.Guna - Logheshwaran, M.S.Guna (2022)
The rapid growth of the population will generate greater demand for housing construction. Throughout the lifespan of a house, the operation phase contributes to an increase in environmental problems such as global warming. This is due to energy usage in the operation phase of a home. To date, the electricity sector in Malaysia is excessively dependent on fossil fuels for electricity generation. The high amount of greenhouse gas (GHC) emissions is being emitted into the atmosphere due to the usage of fossil fuels for electricity generation, which contributes to global warming. Besides that, water usage and waste management also impact the environment during a house's operation phase. With that, a cleaner production strategy was implemented to green the residential area in the planning stage of housing construction. A cleaner production strategy is the continuous application of an integrated preventive environmental strategy to improve the overall efficiency in reducing emissions and wastes. A case study analysis conducted in Taman Templer Suasana residential area found that a small group of respondents practice cleaner production strategies in their homes. From the analysis of the case study, several cleaner production strategy options can be introduced to construct a new house. Twenty-three cleaner production strategies were introduced in greening residential areas in the planning stage of constructing new houses. This strategy compromises energy, water conservation, house design, housekeeping, and material used for constructing a new house.